Study on Circular Economy Pathways for Waste Management in the Philippines - Gregorio Rafael P. Bueta; Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2023)
Solid waste management has been a complex and evolving challenge for the Philippines. Since its passage more than two decages ago, Republic Act No. 9003 or the Ecological Solid Waste Management Act of 2000 has anchored the country's waste management initiatives. But challenges persist in the policy's implementation at both the national and subnational levels. The passage of the Extended Producer Responsibility (EPR) Act of 2022 is a positive step towards improving waste management and achieving a circular economy (CE). But issues remain, including the need for clarity in the scope and definition of CE, operationalization of PROs, setting of costs and fees, role of NGAs and LGUs, program targets, and informal sector participation. Nevertheless, recent policy and institutional developments present avenues for better stakeholder cooperation and collaboration, and the application of technological solutions and innovations. The government needs to focus on bridging critical institutional and implementation gaps including the creation and/or operationalization of the NEC and local solid waste management or environment offices, provision of technology, facilities and waste management resources, and facilitation of public-private partnerships for capital and infrastructure needs.
Keywords: 330; Circular economy; solid waste management; Extended producer reponsibilty